2014
DOI: 10.1155/2014/248403
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Detection Efficiency of LYSO Scintillator in the Fiber-Optic Radiation Sensor

Abstract: The aim of this study was to develop and evaluate fiber-optic sensors for the remote detection of gamma rays in areas that are difficult to access, such as a spent fuel pool. The fiber-optic sensor consists of a light-generating probe, such as scintillators for radiation detection, plastic optical fibers, and light-measuring devices, such as PMT. The (Lu,Y) 2 SiO 5 :Ce(LYSO:Ce) scintillator was chosen as the light-generating probe. The (Lu,Y) 2 SiO 5 :Ce(LYSO:Ce) scintillator has higher scintillation efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In addition, a 40-ns decay time showed that the light yield of the LYSO was approximately four times higher than that of the BGO. Therefore, (Lu,Y) 2 SiO 5 :Ce(LYSO:Ce) has an advantage for the remote detection of gamma rays because of its high light output, high density, fast decay time with good radiation hardness, non-hygroscopic with high effective atomic numbers, and stable physical and chemical properties [107].…”
Section: Other Applications 351 Nuclear Fusion Researchmentioning
confidence: 99%
“…In addition, a 40-ns decay time showed that the light yield of the LYSO was approximately four times higher than that of the BGO. Therefore, (Lu,Y) 2 SiO 5 :Ce(LYSO:Ce) has an advantage for the remote detection of gamma rays because of its high light output, high density, fast decay time with good radiation hardness, non-hygroscopic with high effective atomic numbers, and stable physical and chemical properties [107].…”
Section: Other Applications 351 Nuclear Fusion Researchmentioning
confidence: 99%
“…Compared with the fibre optic dosimeters presented so far, the SPC detector configurations of the presented dosimeter are approximately five-times less sensitive. On the contrary, using PMT, the sensitivity of the presented dosimeter is comparably sensitive or more sensitive [ 19 , 20 ]. Thus, the differences in sensitivity are mainly due to the sensitivity of different detectors and the different optical fibre properties, diameters, and NAs.…”
Section: Measurements and Resultsmentioning
confidence: 99%
“…Nevertheless, in the fibre optic dosimeters published so far, the use of plastic optical fibres predominates [ 17 ]. Plastic fibres with larger diameters, typically 1–3 mm, are often used due to higher NAs, and they are not as fragile as silica optical fibres [ 18 , 19 ]. A common feature of these dosimeters is the adaptation of the diameter of the scintillation material to the diameter of the optical fibre [ 20 , 21 ], the deposition of scintillation material on the surface or inside the optical fibre [ 22 ], or the direct doping of the optical fibre with scintillation material [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, to obtain the signals from these arrays, all the above requires complex peripheral circuits and timing control, which cannot be easily integrated directly on a Si wafer. In addition, both sensing arrays can only sense e-Beam dosage in a real-time fashion which requires power connection or/or battery unit in the sensor modules [29], [30], making their installation onto e-Beam systems more complex and less flexible. In addition, under the e-Beam sensing, with the high optical resolution and high energy e-Beam is found to penetrate deep into the sensing plan, result in serious disturbance on the sensing devices, leading to unexpected damage and/or distortion of the signals.…”
Section: Introductionmentioning
confidence: 99%